An Investigation of BBC Learning English for Listening Tasks in a Computerized Academic - Mega Witjaksana; Sholihatul Hamidah Daulay (Tell : Teaching of English Language and Literature Journal, 2025)
This research aimed to investigate the impact of the BBC Learning English application on listening skills among 10th-grade students in a computerized academic setting. The study involved 46 students from MAS TPI Sawit Seberang, divided into two groups of 23 students each. The experimental group utilized the BBC Learning English application, while the control group received traditional instruction. Employing a quasi-experimental design with pre-tests and post-tests, the experimental group also completed a questionnaire. Statistical analysis revealed significant differences (α = 0.05) in post-test listening scores, favoring the experimental group. Additionally, "strongly agree" and "agree" were the most common responses regarding the application’s usability, indicating a positive effect on students' attitudes. The findings suggest practical applications for integrating technology into English language instruction, highlighting the potential of digital tools like the BBC Learning English application to enhance listening skills. This study contributes to the theoretical framework of English Language Teaching by demonstrating the effectiveness of technology-mediated learning and its impact on student engagement and skill development. Therefore, incorporating the BBC Learning English application into listening skills instruction is recommended.